Migrating to prison: America's obsession with locking up immigrants - García Hernández, César Cuauhtémoc (The New Press, 2019)
Introduction -- Then. Laying the groundwork ; On the prison's edge ; The resurgence of immigration prisons -- Now. The immigration prison archipelago ; The good immigrant vs. the bad immigrant ; The money -- Toward a different tomorrow. Abolishing immigration prisons -- Conclusion.